The family that sings together, Sydney October 9th 2004 - Chapman, Andrew, 1954- (2004)
"'The Family That Sings Together', Sydney October 9th 2004. The Howard family sing the National Anthem at Prime Minister, John Howard's Historic 2004 Federal Election victory acceptance at the Wentworth Hotel, Sydney. This seemed to be a show of the Prime Ministers commitment to traditional family values."--Notes supplied by photographer.
Title devised by photographer.
Also available online
Purchased from the photographer, 2005.
Keywords: Howard, John, -- 1939- -- Portraits; Howard, Janette -- Portraits; Prime ministers -- Australia -- Portraits; Prime ministers' spouses -- Australia -- Portraits; Elections -- New South Wales -- Photographs; Federal politicians; Prime ministers; Politicians' spouses